1998
DOI: 10.1017/s1357729800009243
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolite concentrations in late pregnant ewes as indicators of nutritional status

Abstract: In a feeding experiment $-hydroxybutyrate (BHB), glucose, albumin, total protein, globulin and urea concentrations in the plasma of twin-bearing ewes were analysed. Mature Suffolk cross ewes were given either formic acid (FA)-treated grass silage or grasslmolassed sugar-beet pulp (MSBP) silage in late pregnancy. The experiment commenced on day 91 of pregnancy and the dietary treatments were FA-treated silage (Tl), FA-treated silage + soya-bean meal (SBM) (T2), MSBP silage (T3), MSBP silage + SBM (T4), FA-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Previous studies reported that CLW is a poor indicator of adequate ewe nutrition [43,44] with contradictory reports of the impact of modest (±20%) variations in late pregnancy energy intake on subsequent lamb birth weight [11,23]. However, studies reporting 35% differences in energy intake have reported differing lamb birth weights [45].…”
Section: Combined Litter Weightmentioning
confidence: 99%
“…Previous studies reported that CLW is a poor indicator of adequate ewe nutrition [43,44] with contradictory reports of the impact of modest (±20%) variations in late pregnancy energy intake on subsequent lamb birth weight [11,23]. However, studies reporting 35% differences in energy intake have reported differing lamb birth weights [45].…”
Section: Combined Litter Weightmentioning
confidence: 99%
“…Concentrations of serum metabolites have been commonly utilized to determine the nutritional status of ruminants (Russel & Wright 1983). The effect of feed intake on glucose, NEFA, ketone compounds, triglycerides, b-hydroxybutyrate, albumin, globulin and urea (Patterson et al 1964;Grummer 1995;O'Doherty & Crosby 1998) have been investigated. Studies carried out in sheep and dairy cattle on serum concentrations of NEFA have shown that concentrations of these metabolites increase during periods of energy restriction and also before and after parturition.…”
Section: Introductionmentioning
confidence: 99%
“…The mean estimations of serum glucose concentration will lead to an increase in the treatment groups after birthing; this might be because of the high concentration of glucocorticoid hormones (e.g., cortisol), which instigate an expansion in hepatic gluconeogenesis. A positive relationship between energy supplementation and serum glucose concentration was found by O‘Doherty and Crosby [ 29 ]. Some studies reported an elevation in glucose concentration during late pregnancy and directly after parturition [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 86%